FACTOGRAPHY AND FICTION : (On the discursive and imaginative layer of the diary-novel Sabor poginulih by Dragan Lakićević) (Heritage, 2023)
Dragan Lakićević's novel Sabor poginulih: Svetozar Jovanović's diary-novel is based on the story and then the manuscript of the diary of lawyer Svetozar Jovanović, which he kept during his unique venture from May to October 2000 in his native village of Lutovo in Montenegro: carving the names of all the dead people from Lutovo. Although small in scope, this multi-layered and compositionally complex novel can be read and interpreted from several different poetic aspects, none of which is secondary or less important. The multitude of interpretive perspectives is conditioned by the non-linear concept of storytelling and the change of the narrator's perspective, but above all by the relationship between the factual (documentary) basis of the novel and its fictional (imaginative) superstructure.With the development of the story about Jovanović's unusual venture, we often lose from sight the clear line (which becomes less and less important) between the questions: who is narrating and which sentence is from the diary and which belongs to the author? Although the facts say otherwise, it seems that Lakićević does not have a prototype of a hero in real life on the basis of which he will build a literary character, but that he built the characterization of his literary hero by adding meanings and nuances to what Svetozar Jovanović himself wrote about himself and his venture. That is why the third hero of the novel can be considered to be the monument, around which the story is essentially woven and all the layers and meanings of the novel are interconnected. The story is told in both an imaginative and a discursive key, whereby the imaginative superstructure does not call into question the probability of events and their motivation.
Keywords: Sabor poginulih, diary-novel, factography, fiction, imagination, hero, story